2006
DOI: 10.1111/j.1524-4725.2006.32031.x
|View full text |Cite
|
Sign up to set email alerts
|

Sterile Versus Nonsterile Gloves During Mohs Micrographic Surgery: Infection Rate is not Affected

Abstract: Our study lends support to the contention that clean, nonsterile gloves are safe and effective for use in the tumor extirpation phase of MMS, at a significant cost savings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
71
0
8

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(79 citation statements)
references
References 7 publications
0
71
0
8
Order By: Relevance
“…6,7 More recently, 3 studies have illustrated that this low rate of SSI is achievable without the use of prophylactic antibiotics, finding SSIs in 0.7%, 1.47%, and 1.8% of dermatologic surgeries. [8][9][10] When comparing these studies, each has its own surgical protocol to prevent infection. This variation can also be found when comparing the practices of Mohs surgeons.…”
mentioning
confidence: 99%
“…6,7 More recently, 3 studies have illustrated that this low rate of SSI is achievable without the use of prophylactic antibiotics, finding SSIs in 0.7%, 1.47%, and 1.8% of dermatologic surgeries. [8][9][10] When comparing these studies, each has its own surgical protocol to prevent infection. This variation can also be found when comparing the practices of Mohs surgeons.…”
mentioning
confidence: 99%
“…In studies looking at wisdom tooth extraction and central venous catheter servicing, sterile glove use did not result in lower infections versus patients treated with clean-boxed gloves. 30,31 The low incidence of infections demonstrated in the study of Rhinehart 28 or epidemiologic studies or theoretical rationale. Many items of surgeon's garb date to early part of last century.…”
Section: Relevance Of Data From Inpatient Operatories To Outpatient Pmentioning
confidence: 98%
“…In the chain of transmission, the health workers' role represents a challenge that has been historically recorded in national and international literature (15) . The health worker's hands are recognized as one of the main elements in the chain of transmission.…”
Section: Discussionmentioning
confidence: 99%
“…Studies (4)(5)(6)(7)(8)(9)(10)(11)(12)(14)(15)18) have shown that researchers correlate latex procedure gloves with sterile gloves in cases of infection, and there appears to be no correlation as long as manufacturing, maintenance, and use policies are preserved. Although procedure gloves host bacteria, it appears they are not sufficient to trigger infection when used in the various health care procedures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation